2005
DOI: 10.1261/rna.7950605
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a native hammerhead ribozyme derived from schistosomes

Abstract: A recent re-examination of the role of the helices surrounding the conserved core of the hammerhead ribozyme has identified putative loop-loop interactions between stems I and II in native hammerhead sequences. These extended hammerhead sequences are more active at low concentrations of divalent cations than are minimal hammerheads. The loop-loop interactions are proposed to stabilize a more active conformation of the conserved core. Here, a kinetic and thermodynamic characterization of an extended hammerhead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 51 publications
9
95
0
2
Order By: Relevance
“…The sTRSV natural hammerhead also shows a higher fraction of ligated substrate than the minimal hammerhead, with K eq int ~16 in 1 mM Mg 2+ and 7.3 in 10 mM Mg 2+ (32). Previous studies on a Schistosoma construct similar to the ones used here reaches a maximum of 6% ligated substrate (with a reported K eq int of 17 at 1 mM Mg 2+ ) (39). Thus all of the natural hammerheads have lower values of K eq int than the minimal construct.…”
Section: Comparison Of the Schistosoma Hammerhead With Other Ribozymessupporting
confidence: 52%
See 1 more Smart Citation
“…The sTRSV natural hammerhead also shows a higher fraction of ligated substrate than the minimal hammerhead, with K eq int ~16 in 1 mM Mg 2+ and 7.3 in 10 mM Mg 2+ (32). Previous studies on a Schistosoma construct similar to the ones used here reaches a maximum of 6% ligated substrate (with a reported K eq int of 17 at 1 mM Mg 2+ ) (39). Thus all of the natural hammerheads have lower values of K eq int than the minimal construct.…”
Section: Comparison Of the Schistosoma Hammerhead With Other Ribozymessupporting
confidence: 52%
“…This loop-loop tertiary interaction stabilizes the catalytically active conformation (30), which increases observed cleavage rate constants by up to 50-fold, allowing efficient cleavage even at low concentrations of metal ions (cleavage rate constants of ~0.2 -1.4 min −1 in 100 µM Mg 2+ (28,31,32)). The hammerhead ribozyme from the Schistosoma mansoni satellite DNA (33, 34) is the best characterized of the natural hammerhead systems with data on the cleavage kinetics, global folding by FRET, local and global dynamics by EPR, and cross-linking studies (31,(35)(36)(37)(38)(39). These studies have shown that the formation of the loop-loop tertiary interaction alters the structure, populations of active conformations, global folding and cleavage kinetics of the natural hammerhead, leading to a ribozyme that is readily cleaved under physiological conditions.…”
mentioning
confidence: 99%
“…The extended HHRz from Schistosoma mansoni demonstrates Cd 2+ rescue of P9 and scissile phosphorothioate substitutions, supporting the prediction that inner-sphere coordination of a metal ion to these phosphates is required for efficient catalysis in the stabilized HHRz (Osborne et al 2005). These prior studies were done with mixtures of phosphorothioates and fixed Cd 2+ concentrations and did not provide sufficient basis to determine ground-state affinities of the rescuing metal ions.…”
Section: Introductionmentioning
confidence: 73%
“…1) or biphasic (Eq. 2) model in which A and B represent the extents of cleavage and k obs1 and k obs2 are observed rate constants (Kim et al 2005;Osborne et al 2005). …”
Section: Hhrz Cleavage Assaysmentioning
confidence: 99%
See 1 more Smart Citation